Comprehensive Analysis of Debt Policy, Dividend Policy, and Profitability on Firm Value in the Finance Sector - Kusnanto, Eri; Qalbia, Farah; M, Agil Septiansyah Wijayanto. (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
This research aims to analyze how Debt Policy, Dividend Policy, and Profitability affect to firm valuation. The population comprises finance sector companies from the Indonesia Stock Exchange from 2018 to 2022. Utilizing a purposive sampling method, a sample of 28 companies was selected from a total population of 106 that met the specified criteria. The data were analyzed using multiple linear regression with SPSS 25 to investigate the relationships between Debt Policy, Dividend Policy, Profitability and Firm Value. The results indicate that Debt Policy, Dividend Policy and Profitability significantly impacts on firm value. These findings underscore the importance of strategic financial policies in shaping firm valuation and provide insights into optimizing financial management strategies in the finance sector.